Forward Contract-Based Decoupled Net Present Value - Khanthavit, Anya; Kijkusol , Teetutt (Thailand and The World Economy, 2021)
The decoupled net present value (DNPV) is a popular valuation method for long-term and complex investment projects. It is believed that this method provides a more accurate value than the traditional net present value method. Despite its popularity and accuracy, the DNPV method misvalues projects. This study shows DNPV’s misvaluation by the put–call parity relationship and proposes to replace DNPV’s synthetic insurance contract with a synthetic forward contract on the project’s free cash flow. The forward contract-based DNPV (FDNPV) values the project exactly. In the case study of a gold-mining project, the risk-neutral and FDNPV values are equal, whereas the traditional NPV and DNPV values are lower than the risk-neutral value. This finding demonstrates FDNPV’s exact valuation and DNPV’s misvaluation.